EFFECTS OF DYSTOCIA ON LIPID PEROXIDATION AND ENZYMATIC AND NON-ENZYMATIC ANTIOXIDANTS IN CROSSBRED DAIRY COWS - Yildiz, Hamit; Simsek, Halil; Saat, Nevzat; Yuksel, Murat (Natl Veterinary Research Inst, 2011)
The aim of the study was to evaluate oxidative stress in cows undergoing normal parturition and cows suffering from dystocia. The erythrocytic glutathione peroxidase (GSH-Px) activity, plasma vitamin A and beta-carotene concentrations, and paraoxonase - PONI activity were lowered (P<0.001, P<0.01, 0.05, and 0.05, respectively) in cows with dystocia compared to normal calving cows. The erythrocytic malondialdehyde (MDA) concentration was markedly increased in the dystocia group compared to normal calving group. However, erythrocytic glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD) activites, and plasma vitamin E and MDA concentrations were not significantly changed in the dystocia-affected cows in comparison to eutocia cows. In the difficult calving Cows, there were significant correlations between the activities of GSH-Px and SOD (r=-0.41, P<0.01), plasma beta-carotene levels and paraoxonase activity (r=0.34, P<0.05), body condition score (BCS) and plasma MDA (r=0.46, P<0.05). Similarly in the cutocia cows there were significant correlations between CAT activity and MDA concentration (r=-0.76, P<0.01), levels of plasma beta-carotene and PONI (r=0.58, P<0.01), BCS and MDA concentrations (r=0.50. P<0.05), and BCS and vitamin E (r=0.53. P<0.05) concentrations. These results suggests that evaluation of plasma vitamin A and beta-carotene concentrations, PONI and GSH-Px activities, and MDA concentration seems to be useful in the assessment of dystocia in cows.
Keywords: cows; dystocia; lipid peroxidation products; antioxidants